Citizenship in the United States: the roles of immigrant characteristics and country of origin - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2008)
This study develops and estimates a model of the naturalization process in the US. The model is based on both the characteristics of immigrants and features of their countries of origin. The empirical analysis is based on the 2000 US Census. Both the characteristics of immigrants and the origin-country variables are shown to be important determinants of citizenship status. The individual characteristics that have the most influence are educational attainment, age at migration, years since migration, veteran of the US armed forces, living with family, and spouses' educational attainment. The country of origin variables of most importance are their degree of civil liberties and political rights, GDP per capita, whether the origin country recognizes dual citizenship, and the geographic distance of the origin country from the US.
urn:nbn:de:101:1-2008072352
Keywords: I38; 320; Immigrants; citizenship; country of origin; human capital; Migranten; Staatsangehörigkeit; Migrationstheorie; Schätzung; USA